Effect of Preoperative Intraocular Pressure in Patients with and without Intolerance to Their IOP-Lowering Medication on the Outcome of Trabectome Surgery - Wons J (Dove Medical Press, 2021)
Juliana Wons,1,* Nadine Mihic,2,* Isabel B Pfister,1 Stefano Anastasi,1 Justus G Garweg,1,2 Markus Halberstadt3 1Swiss Eye Institute, Rotkreuz, and Berner Augenklinik am Lindenhofspital, Bern, Switzerland; 2Department of Ophthalmology, University of Bern, Bern, Switzerland; 3Private Practice for Ophthalmology, Flums, Switzerland*These authors contributed equally to this workCorrespondence: Markus HalberstadtAugenärzte Flums, Marktstrasse 21, Flums, 8890, SwitzerlandEmail augenaerzte-flums@hin.chPurpose: This study aimed to compare the effect of trabectome surgery in patients with and without intolerance to their medication and with preoperatively sufficiently controlled, insufficiently controlled, and uncontrolled intraocular pressure (IOP) on the surgical outcome.Patients and Methods: A total of 155 eyes (133 patients) with different forms of open angle glaucoma with or without intolerance to their glaucoma medication undergoing trabectome surgery alone (AIT) or combined with phacoemulsification (phaco-AIT) were included in this retrospective monocentric study. Patients were corresponding to IOP ≤ 18 mmHg (controlled but glaucoma progression or intolerance, group 1), 19– 26 mmHg (insufficiently controlled, group 2), and ≥ 26 mmHg (not controlled, group 3), respectively. Pre- and postoperative IOP and the number of IOP-lowering medications were registered over 12 months. Surgical success was defined as a postoperative IOP of ≤ 18mmHg and/or reduction of the topical treatment demand after 1 year.Results: Of the 155 included eyes, 79 received AIT and 76 received phaco-AIT. Sixty-nine eyes had a preoperatively sufficiently controlled IOP, 63 had an insufficiently controlled IOP, and 23 had an uncontrolled IOP. In all groups, the IOP significantly dropped by 6 and 12 months after surgery (p < 0.001). Surgical success war similar in all groups [47.8% (group 1), 38.1 (group 2) and 34.8% (group 3); p= 0.47]. The effect of AIT on IOP and glaucoma medication independent of intolerance to the anti-glaucoma medication and type of surgery (AIT/phaco-AIT).Conclusion: Independently of the preoperative IOP, a satisfying surgical success was achieved using AIT. In instances that do not qualify for filtrating surgery, trabectome surgery alone or in combination with phacoemulsification thus represents a safe and effective minimally invasive glaucoma surgery technique regardless of an intolerance to the topical medication.Keywords: glaucoma, ab interno trabeculectomy, trabectome, minimally-invasive glaucoma surgery, minimally-invasive glaucoma surgery, MIGS